Ireland : Twelfth Review Under the Extended Arrangement and Proposal for Post-Program Monitoring. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Ireland's Twelfth Review Under the Extended Arrangement and Proposal for Post-Program Monitoring. Ireland has pulled back from a severe banking crisis with the support of the EU-IMF arrangements and broader European initiatives. Though below initial projections, growth has exceeded the euro area average and indicators suggest a recovery may be emerging. Banking reforms have supported financial stability. The crisis and bank support led to a substantial rise in the deficit and a sharp increase in public debt. On the basis of the progress made under Ireland's program, the IMF staff supports the authorities' request for completion of the twelfth review.